Change Laboratory intervention for promoting learning about causes and prevention of workplace aggressions in a mental health facility - Hurtado, Sandra Lorena Beltran; Gardona, Nataly [UNESP]; de Almeida, Ildeberto Muniz [UNESP]; Querol, Marco Antonio Pereira (Elsevier, 2024)
Aim: To assess a Change Laboratory (CL) intervention concerning the promotion of learning about the causes and prevention of workplace aggression in a Healthcare Service for Drug and Alcohol Users. Background: It is estimated that one fourth of all healthcare professionals worldwide have already experienced some kind of workplace violence. In mental health facilities, aggressions have multiple origins, including moments when physical restraint is applied or situations when the patients’ demands are not met. This problem is aggravated in facilities known for their practice of imposing disciplinary measures. Several studies have shown the need to reduce disciplinary means, as well as the importance of health service teams and user participation in designing strategies to prevent aggression. Design: This study employed a qualitative approach with an exploratory and descriptive design. An intervention was conducted in a Healthcare Service for Drug and Alcohol Users, in Brazil. The COREQ guidelines were followed for reporting. Methods: This study is a qualitative analysis of nine sessions of a CL, which was conducted in 2022 with 12 healthcare professionals, mainly women from the nursing staff. Results: These workers identified the main causes of aggression after a historical and empirical analysis of the nature of the work performed and the contradictions inherent within it. They also recognized the need for cooperative teams prepared to recognize potentially aggressive situations beforehand. Conclusions: This article brings practical contributions by showing a detailed analysis of how the CL intervention method, using the principle of Transformative Agency Double Stimulation, promotes a sequence of learning actions. The method helped participants to systematically understand the causes of the situations that give rise to workplace violence, examining the goal of the activity as something socially and historically constructed. Likewise, this method helped the professionals to collectively build the key components of a potential prevention program against aggression in the workplace.
Keywords: Aggression; Exposure to violence; Healthcare Workers; Mental health services; Nursing education; Substance abuse treatment centers; Worker participation; Workplace violence